Agricultural input markets in Ghana: A descriptive assessment of input dealers in eight districts - Asante, Seth; Andam, Kwaw S.; Simons, Andrew M.; Amprofi, Felicia Ansah; Osei-Assibey, Ernest; Iddrisu, Adisatu; Blohowiak, Samuel (International Food Policy Research Institute, 2021)
This paper provides a description of the agricultural input market in Ghana in 2019 across six districts with high maize production and two municipal districts noted for agricultural marketing activities. Since 2017, Ghana’s agricultural has been heavily focused on implementation of the Planting for Food and Jobs (PFJ) program, which has rapidly scaled up the distribution of subsidized seed and fertilizer with the aim of increasing agricultural productivity and production. Agricultural input dealers play a crucial role in the PFJ program as the final node in the supply chain of seed and fertilizer for farmers. Their operations are expected to enhance the availability of and access to these agricultural inputs. Understanding the characteristics and operations of agricultural input dealers can help policymakers to formulate, implement, and reform seed and fertilizer policies. Our study shows low levels of specialization among agricultural input shops, high participation in the sector association, an increase in the entry of traders into the agricultural input market since the launch of PFJ, and a continuing concentration on fertilizer sales compared to seed sales. Major constraints that agricultural input supplier face in expanding their businesses include difficulties in obtaining financial support from the banking sector, still unreliable supplies, and, for subsidized inputs, the slow processing by government of the subsidy vouchers farmers gave them in exchange for inputs.